One Day One Article One Week One Chapter Program in Fostering Students’ Literacy: Implementation and Perception - Rusiana Rusiana; Mutohhar Mutohhar; Nuraeningsih Nuraeningsih; Tono Suwartono (AL-ISHLAH: Jurnal Pendidikan, 2023)
Literacy has been a big concern for the English Education Department. As an effort to prepare the freshmen to be literate and get ready for academic life during their study in undergraduate program, the department enacted a literacy program namely, “One Day One Article One Week One Chapter”. The present research aims to portray the implementation and investigate the students’ perception of the program. This research is qualitative by using observation and questionnaire distribution. The observation was carried out during the implementation of the program. A closed-ended questionnaire, which was developed to determine the students’ perception, was administered at the end of the program to the thirty first-semester students. Based on the observation, it was revealed that the program’s implementation is seen to be applicable as a regular program in the department. Based on the questionnaire, the students’ reading frequency was in the sometimes category; the topic preference was mostly social; the reading source was from online and printed sources; no significant number of students did post-reading activities; and the students read anywhere. The students’ perception of the program was positive in terms of reading importance and reading advantage.